2013
DOI: 10.3109/15376516.2013.848006
|View full text |Cite
|
Sign up to set email alerts
|

In uteroexposure to itraconazole during different gestational periods of rats

Abstract: The present study aimed to investigate the teratogenic and genotoxic effects of itraconazole administered orally to pregnant rats on gestation days 1-7 (implantation), 8-14 (organogenesis) and 14-20 (fetal developmental period) at doses 75, 100 or 150 mg/kg b.wt. The results indicated that itraconazole had embryolethal effect when administered at a dose of 150 mg/kg b.wt throughout implantation and organogenesis periods as well as at 100 mg/kg b.wt during implantation period. Itraconazole elevated the teratoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…These observations may be supported by the study that was done by El‐Shershaby et al. () who found that fetuses whose mothers were treated during the preimplantation‐implantation period with 100 and 150 mg/kg of itraconazole and through the organogenesis period with 150 mg/kg of itraconazole were resorbed early. Furthermore, Tripathi et al.…”
Section: Discussionmentioning
confidence: 65%
See 4 more Smart Citations
“…These observations may be supported by the study that was done by El‐Shershaby et al. () who found that fetuses whose mothers were treated during the preimplantation‐implantation period with 100 and 150 mg/kg of itraconazole and through the organogenesis period with 150 mg/kg of itraconazole were resorbed early. Furthermore, Tripathi et al.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, Vogel and Speilmann (1986) added that during the preimplantation period, defects in DNA repair enzymes and low antioxidant enzyme levels lead to high DNA fragmentation and preimplantation embryos may have a lower capacity for DNA repair than adult tissues. These observations may be supported by the study that was done by El-Shershaby et al (2014) who found that fetuses whose mothers were treated during the preimplantation-implantation period with 100 and 150 mg/kg of itraconazole and through the organogenesis period with 150 mg/kg of itraconazole were resorbed early. Furthermore, Tripathi et al (2008) revealed that the fetus and newborn are more susceptible to genetic damage in comparison to the adult, due to an underdeveloped metabolizing enzyme profile and also due to the decrease in the DNA repair capacity in newborn as compared to adult.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations